Comparative Analysis of LEED Certified Projects in Antalya Within the Scope of Sustainable Building Design - Gözde Çakır Kıasıf (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
LEED Certificate, which is of American origin, is an international evaluation system that reveals the sustainability of buildings. Within the scope of the study, LEED Certified projects in Antalya were scanned and their sustainability was examined. The purpose of the study is to reveal which criteria support the sustainability of projects within the scope of LEED. In addition, the five projects in the sample of the study were compared and their strengths and weaknesses were discussed. In the study, an evaluation was made on the score cards of LEED Certified projects using the descriptive design method. As a result, among these five projects, Güzel Enerji Fuel Station and Otokoç Otomotiv showed the highest success, receiving 73 out of 100 with the LEED O+M: Existing Buildings (v4.1) Gold certificate. Then, the LEED BD+C: Hospitality (v4) Gold certified Kempinski The Dome Belek Villas and the LEED BD+C: New Construction (v4) Gold certified Technopark Administrative Building achieved above average success by receiving 62 points out of 110. Finally, it has been revealed that the LEED BD+C: Hospitality (v4) Silver certified Süral Saray Hotel achieved a success slightly below the average by receiving 50 points out of 110.